Pasien Osteoarthritis Genu dengan Obesitas di Rumah Sakit Universitas Airlangga Surabaya - Sarah Evita Husnah; Andriati Andriati; Teddy Heri Wardhana; Awalia Awalia (Sarana Ilmu Indonesia (salnesia), 2019)
Osteoarthritis is a degenerative disorder, which is characterized by the occurrence of thinning of the cartilage in the joints and causes bones to rub against each other so that stiffness, pain, and movement disorders arise. The condition of obesity can worsen osteoarthritis and cause complications of knee deformity. Objection of this study was to knowing the profile of knee osteoarthritis patients with obesity in the physical medicine and rehabilitation department of Airlangga University Hospital Surabaya. This research is a retrospective descriptive study by taking data from secondary data in the form of medical records for osteoarthritis patients in 2017 at the physical medicine and rehabilitation department of Airlangga University Hospital Surabaya. The results obtained was from a total sample of 36 obese knee osteoarthritis patients, the highest age group was 50-69 years (66,7%), dominated by female (69,4%), patients was grade 1 obese (77,8%), patients had bilateral knee osteoarthritis (47,2%), and the highest severity of osteoarthritis was grade 2 (61,1%). Then obtained osteoarthritis patients with obesity accompanied by knee deformity amounted to 9 people, with the most common deformity was varus deformity (81,25%) from total patients with deformity. Knee osteoarthritis was mostly found in elderly and female. Most patients were grade 1 obesity. More patients with bilateral osteoarthritis with grade 2-3. The knee deformity that more commonly found in patients was varus deformity.